Kemampuan Adaptasi Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) terhadap Berbagai Famili Tanaman Inang pada Musim Kemarau dan Hujan di Bali - KURNIAWATI, AGNESIA; SUPARTHA, I WAYAN; WIJAYA, I NYOMAN (Agrotrop : Journal on Agriculture Science; Vol 13 No 1 (2023)DO - 10.24843/AJoAS.2023.v13.i01.p08, 2023)
The adaptability of Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) to various host families in the dry and rainy seasons in Bali . Leafminer fly Liriomyza trifolii (Burgess) (Diptera: Agromyzidae) is a newly introduced invasive spec thatthatd attacks various types of host plants in Bali. This study aims to determine the adaptability of L. trifolii (Diptera: Agromyzidae) to various host plants during the dry and rainy seasons in Bali. This research was conducted in all regencies/cities in Bali in September 2020-March 2021 using a survey method starting from the lowlands <500 masl, medium plains 500-1000 masl, and highlands > 1000 masl. Sampling was carried out by purposive sampling by taking 100-150 plant leaves showing symptoms of leaf damage by L. trifolii at the study site. The results showed that L. trifolii was able to adapt to damage 10 types of host plants from the Asteraceae family, namely Gumitir flowers, Chrysanthemums and Zinia flowers, Fabaceae family, namely long beans, squat beans, and green beans, Brassicaceae family, namely Pak Choyy and mustard greens, Solanaceae family, namely tomatoes. and the Cucurbitaceae family, namely cucumbers in two growing seasons from the lowlands to the highlands. Gumitir and long bean flowers are the host plants that get the highest attack frequency from L. trifolii during the dry and rainy seasons in Bali, both in the lowlands and in the middle. Gumitir and long bean flowers were indicated as the most selected host plants by L. trifolii in the field. The novel results of this study indicate that L. trifolii is a new invasive pest in Bali that has broad adaptability to host plant families during the rainy and dry seasons in low, medium, and high altitudes.